Finances et developpment. - Relations Dept., International Monetary Fund. External (Finance & Development., 2010)
Prize or Penalty: When Sports Help Economies Score"" looks at why countries vie to host the world's most costly sporting events. And, in a series of articles on ""After the Crisis, "" we discuss why some countries were hit harder than others; how were shocks transmitted round the world, and whether protectionist pressures might intensify in 2010. As usual, we take on a number of hot topics, including housing prices, bankers' bonuses, Ponzi schemes, and inflation targeting. In ""Picture This"" we see that the number of hungry is on the rise, topping 1 billion. Our regular ""People in Economics""